Inhibitory effects of fluoroquinolone antibiotics on Babesia divergens and Babesia microti, blood parasites of veterinary and zoonotic importance - Rizk, Mohamed Abdo (Infect Drug Resist, 2018)
AIM: This study aimed to evaluate the inhibitory effects of fluoroquinolone antibiotics, including enrofloxacin, enoxacin, trovafloxacin, norfloxacin, and ofloxacin, on the in vitro and in vivo growth of Babesia divergens and Babesia microti parasites, respectively. MATERIALS AND METHODS: The in vitro and in vivo inhibitory effects of fluoroquinolone antibiotics against B. divergens and B. microti, respectively were evaluated using fluorescence-based assay. Additionally, combination therapies of highly effective fluoroquinolone antibiotics (enrofloxacin, enoxacin, and trovafloxacin) with diminazene aceturate, luteolin, or pyronaridine tetraphosphate were tested on the in vitro cultures of B. divergens. RESULTS: Enrofloxacin, trovafloxacin, and enoxacin were the most effective fluoroquinolones against the in vitro growth of B. divergens, followed by norfloxacin and ofloxacin. Furthermore, a combination of enoxacin or trovafloxacin with either diminazene aceturate, luteolin, or pyronaridine tetraphosphate significantly enhanced the inhibitory effect on the growth of B. divergens in in vitro cultures. In mice infected by B. microti, enoxacin and diminazene aceturate combination therapy exhibited a potential antibabesial effect. CONCLUSION: These results suggest that safe and cheap fluoroquinolone, such as enoxacin, might be used for the treatment of clinical cases caused by Babesia spp. in animals or humans.